Lower Urinary Tract Dysfunction From Evidence to Clinical Practice - Pang, Ran (IntechOpen, 2020)
Lower urinary tract dysfunction (LUTD) is an umbrella diagnosis that covers the abnormalities of anatomy and function in the bladder, urethra, and, in men, the prostate. People with LUTD face a number of social, mental, and physical health effects due to the symptoms. Despite the increasing evidence in the assessment and management of lower urinary tract symptoms, it remains a challenge to bridge the gap between research evidence and clinical practice. In this book, each and every one of the authors presents a remarkable work for how to apply the evidence to clinical practice from different aspects. I hope this book is a key for every reader to open the door to LUTD.